2018
DOI: 10.3762/bjnano.9.65
|View full text |Cite
|
Sign up to set email alerts
|

The effect of atmospheric doping on pressure-dependent Raman scattering in supported graphene

Abstract: Atmospheric doping of supported graphene was investigated by Raman scattering under different pressures. Various Raman spectra parameters were found to depend on the pressure and the substrate material. The results are interpreted in terms of atmospheric adsorption leading to a change in graphene charge carrier density and the effect of the substrate on the electronic and phonon properties of graphene. It was found that adsorption of molecules from the atmosphere onto graphene doped with nitrogen (electron dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…The G/2D peak intensity histogram (figure 4d) ,in conjunction with the 2D histogram of figure 4c, clearly shows a continuous distribution, where the average G/2D peak intensity ratio is slightly less than 0.5. This is attributed to the sample being slightly p-doped as charge doping is known to enhance (decrease) the G (2D) peak intensity such that the G/2D peak is still indicative of monolayer graphene [72,73]. Similarly, the Figure 4: Surface characterisation of CVD graphene wet transferred onto a silicon substrate.…”
Section: Results Sectionmentioning
confidence: 99%
“…The G/2D peak intensity histogram (figure 4d) ,in conjunction with the 2D histogram of figure 4c, clearly shows a continuous distribution, where the average G/2D peak intensity ratio is slightly less than 0.5. This is attributed to the sample being slightly p-doped as charge doping is known to enhance (decrease) the G (2D) peak intensity such that the G/2D peak is still indicative of monolayer graphene [72,73]. Similarly, the Figure 4: Surface characterisation of CVD graphene wet transferred onto a silicon substrate.…”
Section: Results Sectionmentioning
confidence: 99%
“…Possible sources of such behavior would be adsorbates or substrate-induced effects. Atmospheric adsorbates (oxygen, water) usually result in p-type doping of the graphene [ 59 , 60 , 61 ]. P-type self-doping for graphene transferred onto the SiO 2 substrate occurred due to various surface treatments and residual charges created on the substrate [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, different doping strategies have been highlighted starting from chemical doping during Gr production, after production thermal doping, irradiation induced doping, and adsorption induced doping . A relevant role of the substrate in the doping effect has been guessed and it has been suggested that free standing Gr is subject to minor efficiency of doping as compared to Gr opportunely supported . Furthermore, in many cases it has been evidenced a critical role of Gr‐substrate interaction in tuning the former properties, as well as some criticisms linked to the temperature applied for processing or during the use of devices that can damage the Gr itself .…”
Section: Introductionmentioning
confidence: 99%